2012
DOI: 10.1186/1477-7819-10-251
|View full text |Cite
|
Sign up to set email alerts
|

A pure invasive cribriform carcinoma of the breast with bone metastasis if untreated for thirteen years: a case report and literature review

Abstract: We report a case of pure invasive cribriform carcinoma of the breast, which had been untreated for thirteen years, being found with bone metastasis at initial presentation, because distant metastasis is rarely found in this tumor. A fifty-nine-year-old postmenopausal woman presented with a large left breast mass. Although she had noticed a lump in a left breast thirteen years ago, she had not sought treatment. The tumor had enlarged gradually since from one year before and become ulcerated. The two enlarged ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The study by Colleoni et al ( 8 ) recommended that favorable histotypes (e.g., the tubular, cribriform, mucinous and papillary types) with luminal tumors may be suitable for no therapy or endocrine therapy alone. However, such decisions must be made cautiously, as it is still possible to have local recurrence, as in the present case, or distant (bone) metastasis if not treated ( 7 ). We therefore hypothesize that chemotherapy and radiotherapy remain necessary for high-risk patients.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The study by Colleoni et al ( 8 ) recommended that favorable histotypes (e.g., the tubular, cribriform, mucinous and papillary types) with luminal tumors may be suitable for no therapy or endocrine therapy alone. However, such decisions must be made cautiously, as it is still possible to have local recurrence, as in the present case, or distant (bone) metastasis if not treated ( 7 ). We therefore hypothesize that chemotherapy and radiotherapy remain necessary for high-risk patients.…”
Section: Discussionmentioning
confidence: 95%
“…This result demonstrated that the prognosis of mixed ICC is less favorable than that of the pure form ( 1 , 3 , 15 ). However, pure ICC could also result in distant (bone) metastasis if untreated ( 7 ). In the present study, one patient who received radiotherapy and short-term hormonal therapy without chemotherapy developed local recurrence following breast-conserving surgery, which indicated that adjuvant chemotherapy may play an essential role following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new definition of the World Health Organization (WHO) describes pure ICC as a carcinoma with infiltrating components presenting more than 90% of cells of invasive cribriform pattern. 9 The tumor may present as a frequently occult mass, difficult for radiological detecting. For this reason, the lesions are usually large at presentation although they grow slowly.…”
Section: Invasive Cribriform Carcinomamentioning
confidence: 99%
“…One case report exists of a pure invasive cribriform carcinoma of the breast left untreated for 13 years. 4 Pure cribriform carcinoma is usually low grade and slowly progressive. Our tumor did not display these features, however.…”
Section: Untreated Axillary Node Metastasis Of Occult Breast Primary Six Years After Diagnosismentioning
confidence: 99%